Sense of Place Ruang Terbuka Bersejarah di Perkotaan: (Studi Kasus: Alun-alun Kidul, Yogyakarta) - Tutun Seliari (Nirta Learning Centre, 2025)
Open space becomes an alternative space to seek pleasure in urban communities. Alun-alun Kidul, as a public space that has historical value in the urban area, has become one of the alternative tourist destinations for the people of Yogyakarta and tourists. Sense of place becomes a concept that refers to a person's perception of a place. This study aims to see the sense of place of visitors to Alun-alun Kidul because the perception of visitors is essential for the sustainability of an urban open space that supports a city. The method used in this study is a mixed method, distributing questionnaires to respondents from the people of Yogyakarta and tourists who have visited Alun-alun Kidul. The analysis was carried out by interpreting respondents' answers with coding. The results of the study show that the sense of place of Alun-alun Kidul includes physical elements including banyan trees, buildings, open fields, forts, pedestrian paths; activity elements including masangin, decorated vehicles, culinary, hanging out, sports; and elements of meaning/image including memory, social space, pleasure, history. Alun-alun Kidul is not only a physical area but also a space for social interaction, recreation, and cultural space.